Anthropogenic‐driven rapid shifts in tree distribution lead to increased dominance of broadleaf species - Jordi Vayreda; Jordi Martinez‐Vilalta; Marc Gracia; Josep G. Canadell; Javier Retana (Global Change Biology, 2016)
Over the past century, major shifts in the geographic distribution of tree species have occurred in response to changes in land use and climate. We analyse species distribution and abundance from about 33 000 forest inventory plots in Spain sampled twice over a period of 10–12 years. We show a dominance of range contraction (extinction), and demographic decline over range expansion (colonization), with seven of 11 species exhibiting extinction downhill of their distribution. Contrary to expectations, these dynamics are not always consistent with climate warming over the study period, but result from legacies in forest structure due to past land use change and fire occurrence. We find that these changes have led to the expansion of broadleaf species (i.e. family Fagaceae ) over areas formerly dominated by conifer species (i.e. family Pinaceae ), due to the greater capacity of the former to respond to most disturbances and their higher competitive ability. This recent and rapid transition from conifers to broadleaves has important implications in forest dynamics and ecosystem services they provide. The finding raises the question as to whether the increasing dominance of relatively drought‐sensitive broadleaf species will diminish resilience of Mediterranean forests to very likely drier conditions in the future.

Estimating cropland carbon mitigation potentials in China affected by three improved cropland practices - Fei Lun; Josep G. Canadell; Lu He; Bo Yang; Mou-cheng Liu; Zheng Yuan; Mi Tian; Jun-guo Liu; Wen-hua Li (Journal of Mountain Science, 2016)